Alibaba Group's Taobao : from intermediary to ecosystem enabler - Williamson, Peter J., (SAGE knowledge. Cases., 2016)
This case explores how Alibaba Group has nurtured the creation of a business ecosystem to underpin the success of its Taobao Marketplace and Tmall.com e-commerce businesses that have come to dominate on-line shopping in China.